Understanding Law and Society in Legal Sociology Studies - Muhammad Watif; Fatwa Atira; Dyah Khafifa Irwana; Jusnianti; Sulistiawati (Pustaka Digital Indonesia, 2024)
This study discusses understanding law and society in the study of legal sociology. Sociology of law is a branch of sociology that examines the relationship between law, legal institutions, and society. The main focus is how law is influenced by and influences social structures, culture, and human behavior. Apart from that, this study highlights the function of law for society, namely functioning as social control, a tool for changing society, as a symbol, political tool and integrator. Law and society cannot be separated. Their existence reinforces and strengthens each other. Indeed, we must consider the sociological component of society when developing legislation. Society and law are two entities that support and encourage each other in achieving the goals of human existence. If there is society, there will be laws. However, if the law is obeyed, society's goals can be achieved